Pemanfaatan Microservice dengan GraphQL Federation Concept untuk Pengembangan Sistem Informasi Akademik (xSIA) - Poetri Lestari Lokapitasari Belluano; Benny Leonard Enrico P; Purnawansyah Purnawansyah; Amaliah Faradibah; Rahmadani Rahmadani (Universitas Ngeri Malang, 2023)
Academic Information System (xSIA) is an application built to manage academic value transaction modules that make it easy for users to manage grades in online academic administration activities. The need for reconstruction of the xSIA microservice architecture from the previously built domain driven design model using the json (javascript object notation) data format, REST (Representational State Transfer and an architectural style for distributed hypermedia systems) communication protocol, authorization and authentication processes occur in each microservice , there is a pooling of data that is charged to the client which has caused the client to make many requests to the various available microservices, as well as making documentation if there are additional microservices. The xSIA system reconstruction was developed by changing the xSIA microservice architecture so that the concept of responsibility authorization and authentication can be carried out according to service needs. The approach to reconstructing the microservice architecture in the xSIA application uses a new concept with the single gateway microservice model and is built using the GraphQL Federation to facilitate data communication between the backend and frontend of the application and can be implemented in various programming languages to minimize downtime when modification process occurs. The results of this study are the xSIA application on the study plan transaction module (krs) using the GraphQL Federation Concept with the single gateway microservice model so that authorization and authentication responsibilities can be carried out according to service requirements with a realtime average of 373.15 milliseconds. Sistem Informasi Akademik (xSIA) adalah aplikasi yang dibangun untuk mengelola modul transaksi nilai akademik yang memberikan kemudahan kepada pengguna mengelola nilai dalam kegiatan administrasi akademik secara online. Kebutuhan rekonstruksi arsitektur microservice xSIA dari model domain driven design yang dibangun sebelumnya menggunakan format data json (javascript object notation), protokol komunikasi REST (Representational State Transfer and an architectural style for distributed hypermedia systems), terjadi proses otorisasi dan otentikasi yang ada di setiap microservice, terdapat penyatuan data yang dibebankan kepada client telah menyebabkan client harus melakukan banyak request ke berbagai microservice yang tersedia, serta pembuatan dokumentasi jika ada penambahan microservice. Rekonstruksi sistem xSIA dikembangkan dengan mengubah arsitektur microservice xSIA sehingga konsep responsibility autorisasi dan autentifikasi dapat dilakukan sesuai dengan kebutuhan service. Pendekatan dalam melakukan rekontruksi arsitektur microservice pada aplikasi xSIA menggunakan konsep baru dengan model single gateway microservice (layanan satu gerbang) dan dibangun menggunakan GraphQL Federation untuk mempermudah komunikasi data antara backend dan frontend dari aplikasi, serta dapat diimplementasikan di berbagai Bahasa pemrograman sehingga meminimaliasir terjadinya downtime saat proses modifikasi terjadi. Hasil penelitian ini berupa aplikasi xSIA pada modul transaksi rencana studi (KRS) menggunakan GraphQL Federation Concept dengan model single gateway microservice sehingga responsibility autorisasi dan autentifikasi dapat dilakukan sesuai dengan kebutuhan service dengan rerata realtime 373.15 millisecond.